Modeling Risk Management in Sustainable Construction - Wu, Desheng Dash.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
In this edited volume, we present the state-of-the-art views of the perspective of enterprise risk management,to include frameworks and controls in the ERM process with respect to supply chains, constructions, and project, energy, environmental and sustainable development risk management. The bulk of this volume is devoted to presenting a number of modeling approaches that have been (or could be) applied to enterprise risk management in construction.
Enterprise Risk-Management in Supply Chains -- Enterprise Risk Management in Construction -- Enterprise Risk Management in Projects -- Energy Risk Management -- Environmental Risk Management -- Financial Risk -- Sustainable Risk Management Tools -- Enterprise Risk Management Modeling.
Keywords: Economics; Operations research; Economics/Management Science; Operation Research/Decision Theory; Production/Logistics/Supply Chain Management